Implementasi Kebijakan Pemenuhan Hak Beragama Penyandang Disabilitas oleh Negara Perspektif Maqashid Syariah - Yasin, Noer (Fakultas Syariah, 2021)
Abstract: The fulfillment of the rights of persons with disabilities is a public concern. Various regulations have been issued to guarantee the rights of persons with disabilities. One of them is the right to have a body in the public space. However, the implementation of these regulations has not run optimally. This article aims to analyze the implementation of the policy on the religious rights of persons with disabilities and the factors that hinder its fulfillment. In addition, this article also describes what solution steps need to be taken in order to provide legal protection for the fulfillment of the right of worship accessibility for persons with disabilities in Malang City from a maqashid sharia perspective. This article is a doctrinal law research with a sociological approach. Primary data were obtained directly through interviews, while secondary data were obtained through documentation. The results of this study indicate that the state has protected the rights of persons with disabilities through Law Number 39 of 1999, Law Number 8 of 2016, Regional Regulation of Malang City Number 2 of 2014, Regional Regulation Number 4 of 1997. However, the implementation of this regulation encountered obstacles. because of the lack of socialization and coordination between the government and the community. The fulfillment of the right of accessibility for persons with disabilities in carrying out worship at the Malang City Mosque is part of the primary sharia maqashid, in particular maintaining religion (hifz al-din) and honoring persons with disabilities as human beings.Keywords: disabilites; religious right; maqashid syariah.Abstrak: Pemenuhan hak penyandang disabilitas menjadi perhatian masyarakat. Berbagai regulasi telah dikeluarkan untuk menjamin hak-hak penyandang disabilitas. Salah satunya adalah hak beribadan di ruang public. Namun, implementasi peraturan tersebut belum berjalan maksimal. Artikel ini bertujuan menganalisis pelaksanakaan kebijakan hak beragama penyandang disabilitas dan faktor-faktor penghambat pemenuhannya. Selain itu, artikel ini juga mendeskripsikan langkah solutif apa yang perlu diambil dalam rangka memberikan perlindungan hukum bagi pemenuhan hak aksesibilitas ibadah bagi penyandang disabilitas di Kota Malang perspektif maqashid syariah. Artikel ini merupakan penelitian hukum doctrinal dengan pendekatan sosiologis.Â Data-data yang bersifat primer diperoleh secara langsung melalui wawancara sedangkan data sekunder diperoleh melalui dokumentasi. Hasil penelitian ini menunjukkan bahwa negara telah melindungi hak-hak penyandang disabilitas melalui Undang-Undang Nomor 39 Tahun 1999, Undang Nomor 8 Tahun 2016, Peraturan Daerah Kota Malang Nomor 2 Tahun 2014, Peraturan Daerah Nomor 4 Tahun 1997. Namun implementasi regulasi ini menemui kendala karena kurangnya sosialisasi dan koordinasi antara pemerintah dengan masyarakat. Pemenuhan hak aksesibilitas bagi penyandang disabilitas dalam melaksanakan ibadah di Masjid Kota Malang adalah merupakan bagian dari maqashid syariah primer, khususnya memelihara agama (hifz al-din) dan kehormatan penyandang disabilitas sebagai manusia.Kata Kunci: disabilitas; hak beragama; maqashid syariah.